Synthesis, characterization and properties of a novel energetic ionic salt: dicarbohydrazide bis[3-(5-nitroimino-1, 2, 4-triazole)]. (4th April 2019) - Ren, Jianrong; Chen, Dong; Fan, Guijuan; Xiong, Ying; Zhang, Zhenqi; Yu, Yanwu; Li, Hongzhen
Abstract : DCBNT, a new compound, exhibits low friction and impact sensitivities, good thermal stability, and promising detonation pressure and detonation velocity. Abstract : Dicarbohydrazide bis[3-(5-nitroimino-1, 2, 4-triazole)] (DCBNT ) was firstly synthesized by ion exchange and salt formation reaction. A combination of single-crystal X-ray diffraction (SXRD), FTIR, 1 H NMR, 13 C NMR, and elemental analysis was utilized to analyze the structure and composition ofDCBNT .DCBNT exhibits a high detonation velocity of 9234.87 m s −1 and a detonation pressure of 31.73 GPa as calculated by EXPLO5 v6.02 program. In addition, the sensitivities (impact sensitivity >40 J, H 50 = 90 cm, and friction sensitivity = 216 N) and thermal stability (>230 °C) ofDCBNT were investigated. Moreover, we measured the solubility ofDCBNT in 12 common solvents by a polythermal method system which demonstrates its poor solubility in common organic solvents and water. These excellent physicochemical properties makeDCBNT an environmentally friendly, low-sensitivity and high-energy explosive.